(untitled) (Teología, 2022)
In this paper we will reflect on integral ecological spirituality, and its possibility that, regardless of religious peculiarities and differences or diverse spiritual experiences, it may be a key to ethical education, overcoming the crisis of meaning and the search for universal fraternity. Methodologically, we will carry out a bibliographic analysis based on the encyclicals Laudato Si ’and Fratelli Tutti, and other theological contributions, in dialogue with other knowledge and disciplines. The development will be structured in three interrelated moments: first we will begin by analyzing the "imperial way of life" and the crisis of meaning, seeing the restorative function that education can exert; in a second moment we will see, with a fundamental axis in Laudato Si’ put into dialogue, education in ethics for integral ecology and why the invitation to an ecological conversion and spirituality in that context; finally, we will see the proposal of Fratelli Tutti in the construction of a universal fraternity and the fundamental role that education will have there.